Do the same genes predispose to Gilles de la Tourette syndrome and dystonia? Report of a new family and review of the literature. - Németh, A; Mills, K; Elston, J; Williams, A; Dunne, E; Hyman, N (1999)
Gilles de la Tourette syndrome (TS) and idiopathic focal torsion dystonia are both movement disorders in which the pathologic process is thought to arise within the basal ganglia. However, despite their possible functional links, they are clinically distinct and are generally considered to have different underlying etiologies. There are several reports in the literature that suggest a relationship between eye winking tics, excessive blinking, and blepharospasm and a report of the coexistence of tics and dystonia. We describe a three-generation family in which TS and dystonias cosegregate. In total, eight patients were affected, five with dystonia and three with TS/facial tics. One of the patients with historic evidence of dystonia subsequently died of motor neuron disease. The identification of this family further strengthens the evidence in favor of an etiologic relationship between some cases of Gilles de la Tourette syndrome and focal dystonia.